Dukungan Organisasi Persepsian, Stres Kerja, dan Intensi Berpindah Tempat Kerja - Andreas Vernando; Ahmad Rizal Solihudin (Universitas Negeri Padang, 2024)
The high external auditor turnover phenomenon has triggered previous researchers to investigate it. The high level of auditor turnover causes inefficiencies for public accounting firms. This study examines whether there is a negative relationship between perceived organizational support and turnover intentions and analyses whether burnout mediates this relationship. This research obtained 57 samples analysed by using structural equation modelling (SEM), which was processed using Stata 14 software. This research documents that perceived organizational support is negatively correlated with turnover intentions. Furthermore, job stress was found to be able to mediate the association between perceived organizational support and turnover intention.